Editorial: Uncomfortable geographies. (February 2022) - Owen, Jennifer; Walker, Amy; Ince, Anthony
Highlights: An introduction to the Special Issue: Uncomfortable Geographies. Focuses on three prominent themes: identity and different, embodiment and practices, and methodological enquiry. Argues for discomfort as an opportunity for enacting political change.